Russian education in the field of commerce: aspects of formation - S. A. Kalugina; A. A. Makarov; T. P. Lebedeva (Путеводитель предпринимателя, 2020)
The article provides a brief history of the development of business education in Europe and Russia XVII - early XX centuries. Described some features of the commercial origin of education, types of educational institutions, the dynamics of their development, aspects of the educational process, the role and importance of entrepreneurs in financing it.